How the Internet really works : an illustrated guide to protocols, privacy, censorship, and governance - Uhlig, Ulrike; Knodel, Mallory (No Starch Press, 2020)
""A comic-based introduction to the technical side of the internet, including transport protocols and basic internet infrastructure. Also explains broader concepts such as security and privacy in the context of the internet"-Provided by publisher"--